Regulation of Neutrophil Survival/Apoptosis by Mcl-1 - Eric Milot; János G. Filep (The Scientific World Journal)
Neutrophil granulocytes have the shortest lifespan among leukocytes in the circulation and die via apoptosis. At sites of infection or tissue injury, prolongation of neutrophil lifespan is critical for effective host defense. Apoptosis of inflammatory neutrophils and their clearance are critical control points for termination of the inflammatory response. Evasion of neutrophil apoptosis aggravates local injury and leads to persistent tissue damage. The short-lived prosurvival Bcl-2 family protein, Mcl-1 (myeloid cell leukemia-1), is instrumental in controlling apoptosis and consequently neutrophil lifespan in response to rapidly changing environmental cues during inflammation. This paper will focus on multiple levels of control of Mcl-1 expression and function and will discuss targeting Mcl-1 as a potential therapeutic strategy to enhance the resolution of inflammation through accelerating neutrophil apoptosis.